Thrombocytosis of active rheumatoid disease. Issue 5 (October 1983) - Farr, M; Scott, D L; Constable, T J; Hawker, R J; Hawkins, C F; Stuart, J
Abstract : Two cross-sectional and one longitudinal study of patients with rheumatoid arthritis showed that platelet number correlated with both clinical and laboratory parameters of disease activity, including erythrocyte sedimentation rate, zeta sedimentation ratio, viscosity of plasma and blood, white cell count, liver enzymes, rheumatoid factor, and several acute-phase proteins. There was also an inverse relationship between platelet number and the haemoglobin and serum albumin levels. III Indium-labelled platelet survival was reduced in 4 patients with active rheumatoid arthritis despite a raised platelet count, with labelled platelets being localised to inflamed joints in the 2 patients studied. Platelet aggregation was normal. We suggest that the raised platelet count of active rheumatoid arthritis may be a useful index of disease activity and may represent a bone marrow stress (syndrome) response to shortened platelet survival, with platelet sequestration occurring in areas of synovial inflammation.